The Contribution of Sports Event To The Income Level of Locals Around (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
Organizing sports eventts or sports matches both multi-sport eventt like Popnas, PON, Sea Games or and single sport eventts such as the National Championship pool KU, Indonesia super league football, and so forth, can bring a variety of resPONses, opinions, and influence of the organization of eventts , including the effect on the income level of the surrounding population. The method used is descriptive qualitative. Results of the analysis showed that the management of sporting eventts in general have konstribusi or contribute to the income level of the surrounding population. Big contribution varies, depending on the scope and level of sporting eventts held, at the levels of International, National, Regional and district / city, a sport which was held, when the organization of sporting eventts, the factor of promotion or dissemination organizing eventts, precision types, kinds and models as well as the quality of the goods or services were sold before, during and after sporting eventts took place. Large sporting eventts contribute to the income level of the surrounding population, in general increases ranging from 15% - 35%. Conclusion, sporting eventts contributes to the income level of the surrounding population.